(untitled) (Scientific journal of the Fergana State University, 2023)
In the article natural -geographical, social -economical and logistics opportunities if Central Asia’s states have been considered. The research on the theme concept " Central Asia: its borders, territory have been analyzed. Natural -geographical conditions, social -economical development level, logistics opportunities of countries located in the region have been considered.Wnen analyzing processes in the region being considered in the article, analyses and synthesis, historical logical, comparative study, general conclusion methods have been used.